Circulating insulin-like growth factor-1 and risk of lung diseases: A Mendelian randomization analysis - Jiang, Sujing; Xu, Zhiyong; Shi, Yueli; Liang, Sibei; Jiang, Xinyuan; Xiao, Mingshu; Wang, Kai; Ding, Liren (Frontiers in Endocrinology, 2023)
Background Insulin-like growth factor-1 (IGF-1) display a vital role in in the pathogenesis of lung diseases, however, the relationship between circulating IGF-1 and lung disease remains unclear. Methods Single nucleotide polymorphisms (SNPs) associated with the serum levels of IGF-1 and the outcomes data of lung diseases including asthma, chronic obstructive pulmonary disease (COPD), lung cancer and idiopathic pulmonary fibrosis (IPF) were screened from the public genome-wide association studies (GWAS). Two-sample Mendelian randomization (MR) analysis was then performed to assess the independent impact of IGF-1 exposure on these lung diseases. Results Totally, 416 SNPs related to circulating IGF-1 levels among 358,072 participants in UK Biobank. According to a primary casual effects model with MR analyses by the inverse variance weighted (IVW) method, the circulating IGF-1 was demonstrated a significantly related with the risk of asthma (OR, 0.992; 95% CI, 0.985-0.999, P=0.0324), while circulating IGF-1 showed no significant correlation with CODP (OR, 1.000; 95% CI, 0.999-1.001, P=0.758), lung cancer (OR, 0.979, 95% CI, 0.849-1.129, P=0.773), as well as IPIGFF (OR, 1.100, 95% CI, 0.794-1.525, P=0.568). Conclusion The present study demonstrated that circulating IGF-1 may be causally related to lower risk of asthma.